A Chemically Defined, Xeno- and Blood-Free Culture Medium Sustains Increased Production of Small Extracellular Vesicles From Mesenchymal Stem Cells - Figueroa-Valdés, Aliosha I.; de la Fuente, Catalina; Hidalgo, Yessia; Vega-Letter, Ana María; Tapia-Limonchi, Rafael; Khoury, Maroun; Alcayaga-Miranda, Francisca (Frontiers in Bioengineering and Biotechnology, 2021)
Cell therapy is witnessing a notable shift toward cell-free treatments based on paracrine factors through cell’s secretome use and in particular, small extracellular vesicles (sEV), that mimic the functional effect of the parental cells. While numerous sEV-based applications are currently in advanced preclinical stages, their promising translation depends on overcoming the manufacturing hurdles posed by the large-scale production of purified sEV. Unquestionably, the culture medium used with the parental cells plays a key role in the sEV’s secretion rate and content. An essential requisite is the use of a serum-, xeno-, and blood-free medium to meet the regulatory entities requirements of clinical grade sEV’s production. Here, we evaluated OxiumTMEXO, a regulatory-complying medium, with respect to production capacity and conservation of the EV’s characteristics and functionality and the parental cell’s phenotype and viability. A comparative study was established with standard DMEM and a commercially available culture medium developed specifically for sEV production. Under similar conditions, OxiumTMEXO displayed a 3-fold increase of sEV secretion, with an enrichment of particles ranging between 50-200nm. These results were obtained through direct quantification from the conditioned medium to avoid isolation method’s interference and variability, and were compared to the two-culture media under evaluation. The higher yield obtained was consistent with several harvest time points (2, 4 and 6 days) and different cell sources, including umbilical cord- and menstrual fluid-derived mesenchymal stromal cells and fibroblasts. Additionally, the stem cell phenotype and viability of the parental cell remained unchanged. Furthermore, OxiumTMEXO-sEV showed a similar expression pattern of the vesicular markers CD63, CD9 and CD81, with respect to sEV derived from the other conditions. The in vitro internalization assays in different target cell types and the pharmacokinetic profile of intraperitoneally administered sEV in vivo indicated that the higher EV’s production rate did not affect the uptake kinetics nor the systemic biodistribution in healthy mice. In conclusion, the OxiumTMEXO medium sustains an efficient and robust production of large quantities of sEV, conserving the classic functional properties of internalization into acceptor target cells and biodistribution in vivo, supplying the amount and quality of EVs for the development of potentially cell-free therapies.